2022
DOI: 10.3390/toxics10040186
|View full text |Cite
|
Sign up to set email alerts
|

A Meta-Analysis of the Characterisations of Plastic Ingested by Fish Globally

Abstract: Plastic contamination in the environment is common but the characterisation of plastic ingested by fish in different environments is lacking. Hence, a meta-analysis was conducted to identify the prevalence of plastic ingested by fish globally. Based on a qualitative analysis of plastic size, it was determined that small microplastics (<1 mm) are predominantly ingested by fish globally. Furthermore, our meta-analysis revealed that plastic fibres (70.6%) and fragments (19.3%) were the most prevalent plastic c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 201 publications
0
11
0
Order By: Relevance
“…The unpredictable fate of MPs in the aquatic environment could explain the different frequencies of both polymers and colors observed among the different sampling sites. Interestingly, within the MP shapes identified, no fibers were observed, although they have been reported as the most frequent MP types ingested by marine animals [44]. The absence of MP fibers in cuttlefish embryos and yolk is probably related to their usually large size which represents a limitation to their transfer within the biological compartments.…”
Section: Discussionmentioning
confidence: 90%
“…The unpredictable fate of MPs in the aquatic environment could explain the different frequencies of both polymers and colors observed among the different sampling sites. Interestingly, within the MP shapes identified, no fibers were observed, although they have been reported as the most frequent MP types ingested by marine animals [44]. The absence of MP fibers in cuttlefish embryos and yolk is probably related to their usually large size which represents a limitation to their transfer within the biological compartments.…”
Section: Discussionmentioning
confidence: 90%
“…Only accidental ingestion of EPS with a size less than 2.5 mm poses a risk to this species. The literature review revealed (Lim et al 2022) that sh mostly ingested microplastic with size < 1 mm. Coral sh Acanthochromis polyacanthus frequently grasped plastic less than 0.3 mm in size, because they do not detect a foreign object and consume it with food (Critchell and Hoogenboom 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Plastic microfragments and microfilms but no spheres were detected in fish GITs as well as in the water and sediments of the river. Meta-analysis recently showed that the largest percentage of MPs ingested by fish was in the form of fibers and fragments [ 53 ].…”
Section: Discussionmentioning
confidence: 99%